Puerariae lobatae Radix aqueous extract ameliorates asymptomatic hyperuricemia in a potassium oxonate-induced rat model by dual modulation of uric acid production and excretion - Zhao, Danping; Wang, Yuannan; He, Tingting; Chen, Yingna; Bai, Yu; Huang, Yuchun; Ding, Kaiyue; Ma, Junnan; Zhang, Lin (Frontiers in Nutrition, 2025)
BackgroundPuerariae lobatae Radix (PLR) is a well-known traditional Chinese medicine and edible natural nutrient, with diverse biological activities, including anti-diabetes, anti-inflammatory, anti-oxidant and liver protection. However, the effects and underlying mechanisms of PLR in hyperuricemia (HUA) are unclear.MethodsThe present study focused on the regulatory effects of aqueous extract from PLR on the asymptomatic hyperuricemia rat model, induced by potassium oxonate. Serum uric acid (SUA), serum blood urea nitrogen (BUN), creatinine (CRE), serum inflammatory factors, anthine oxidase activity, hepatic and renal tissue morphology were measured to assess the anti-hyperuricemia effect. After which, 16SrDNA sequencing and the UHPLC-Q-Orbitrap-MS/MS with network pharmacology, qRT-PCR and molecular docking were employed to elucidated the potential mechanism.ResultsPLR treatment led to a significant improvement in HUA rats, including lower SUA, BUN, CRE and serum inflammatory factors (TNF-α, IL-6, IL-1β, and NF-κB); inhibited xanthine oxidase activity like xanthine oxidase (XOD), Adenosine deaminase (ADA), regulated the abundance of Firmicutes, Actinobacteriota and Bacteroidota. And the network pharmacological analysis combined with qRT-PCR and molecular docking revealed 4 active compounds of PLR, including hispidulin, cirsimaritin, galangin, and diosmetin, that act on HUA therapeutic targets, like CASP3, NF-κB, PTGS2, PARP1 and JAK2.ConclusionOur finding suggest that PLR could effectively ameliorate HUA symptoms by modulating multiple compounds, targets, and pathways. Specifically, hispidulin, cirsimaritin, galangin, and diosmetin are proposed as the key active ingredients in PLR for HUA alleviation. The primary mechanism involves inhibiting xanthine oxidase activity to reduce UA production, promoting UA excretion by restoring the abundance of intestinal flora, and eliminating the negative feedback regulatory mechanism of renal tissue. This study provided a new perspective for the precise exploitation of PLR as a functional food.